2019
DOI: 10.3390/en12101853
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Comparison of Some Low-Temperature Heat Sources for Heat Pumps

Abstract: The efficiency of a heat pump energy system is significantly influenced by its low-temperature heat source. This paper presents the results of operational monitoring, analysis and comparison of heat transfer fluid temperatures, outputs and extracted energies at the most widely used low temperature heat sources within 218 days of a heating period. The monitoring involved horizontal ground heat exchangers (HGHEs) of linear and Slinky type, vertical ground heat exchangers (VGHEs) with single and double U-tube exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The efficiency of a heat pump's energy system is greatly influenced by a low-temperature heat source. Neuberger and Adamovský [7] presented the results of operational monitoring, analysis and comparison of temperatures, power and energy of antifreeze fluid in the most commonly used low-temperature heat sources. The results of the verification indicated that it was not possible to unequivocally define the most favorable low-temperature heat source meeting the requirements for the efficiency of the heat pump operation.…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of a heat pump's energy system is greatly influenced by a low-temperature heat source. Neuberger and Adamovský [7] presented the results of operational monitoring, analysis and comparison of temperatures, power and energy of antifreeze fluid in the most commonly used low-temperature heat sources. The results of the verification indicated that it was not possible to unequivocally define the most favorable low-temperature heat source meeting the requirements for the efficiency of the heat pump operation.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to the laboratory results obtained from these studies, it is possible to determine the optimal pattern of behavior for entire vertical closed systems [33]. Neuberger and Adamovský [34] presented the results of operational monitoring, analysis and comparison of temperatures, power, and energy of antifreeze in the most commonly used low-temperature heat sources. The results of the verification showed that it was not possible to unequivocally define the most advantageous low-temperature heat source that meets the requirements for the efficiency of heat pump operation.…”
Section: Introductionmentioning
confidence: 99%
“…Neuberger and Adamovsky [7,8] conducted measurements of the ground temperature near the slinky-coil and straight pipe exchangers. The research was conducted both during the heating season and for the thermal regeneration of the ground.…”
Section: Introductionmentioning
confidence: 99%